INTEGRASI NILAI MORAL DAN KARAKTER KRISTIANI DALAM PEMBELAJARAN ANAK USIA DINI DI ERA MODERN - Hasni Bandangan (CV. Adiba Aisha Amira, 2026)
This study aims to describe and analyze the integration of Christian moral and character values ​​in early childhood education in the modern era. The background of this study is based on the importance of the golden age as a foundation for character formation, as well as the increasing challenges due to technological developments, globalization, and shifts in social values ​​that have an impact on children's moral degradation. This study uses a library study method by reviewing various literature in the form of books and journals relevant to character education, children's moral development, and Christian education. The results of the study indicate that the integration of Christian moral and character values ​​cannot be done purely theoretically, but must be through a holistic, contextual, and applicable approach. Values ​​such as love, honesty, forgiveness, and responsibility need to be instilled through direct experience, teacher role models, social interactions, and the use of creative Bible-based learning methods. Teachers have a strategic role as educators and spiritual role models in the process of internalizing these values. In addition, this study found that there is still a gap between the ideal concept of Christian character education and its implementation in the field, especially in the use of digital technology. Therefore, synergy is needed between schools, families, and communities to support the optimal formation of children's character. With effective integration, Christian education is expected to shape a generation that is not only intellectually intelligent but also possesses strong character and faith to face the challenges of the modern era.